Splitting Things Apart to Put Them Back Together Again: A Targeted Review and Analysis of Psychological Therapy RCTs Addressing Recovery From Negative Symptoms - McLeod, Hamish J. (Frontiers in Psychiatry, 2022)
Negative symptoms have attracted growing attention as a psychological treatment target and the past ten years has seen an expansion of mechanistic studies and clinical trials aimed at improving treatment options for this frequently neglected sub-group of people diagnosed with schizophrenia. The recent publication of several randomised controlled trials of psychological treatments that pre-specified negative symptoms as a primary outcome warrants a carefully targeted review and analysis, not least because these treatments have generally returned disappointing therapeutic benefits. This mini-review dissects these trials and offers an account of why we continue to have significant gaps in our understanding of how to support recovery in people troubled by persistent negative symptoms. Possible explanations for mixed trial results include a failure to separate the negative symptom phenotype into the clinically relevant sub-types that will respond to mechanistically targeted treatments. For example, the distinction between experiential and expressive deficits as separate components of the wider negative symptom construct points to potentially different treatment needs and techniques. The ten negative symptom-focused RCTs chosen for analysis in this mini-review present over 16 different categories of treatment techniques spanning a range of cognitive, emotional, behavioural, interpersonal, and metacognitive domains of functioning. The argument is made that treatment development will advance more rapidly with the use of more precisely targeted psychological treatments that match interventions to a focused range of negative symptom maintenance processes.